Alternative hosts of banana bunchy top virus in the Philippines and the first evidence of seed transmission of BBTV - Mendoza, Nicole Angelee P.; Mendoza, Jay-Vee S.; Thomas, John E.; Dela Cueva, Fe M. (Frontiers in Plant Science, 2024)
BBTV is transmitted locally by aphids (Pentalonia spp.), but the long-distance spread is through the movement of infected planting materials. This study investigated potential alternative hosts of BBTV in ornamental Musa and related species in the Zingiberales in the Philippines. The potential for seed transmission of BBTV through Canna indica seeds was also investigated. Typical symptoms of BBTV in bananas, including dark green streak on the midrib and petiole and rosetting were observed on inoculated Musa coccinea (banana blossom), M. velutina (velutina), M laterita. (bronze banana) and Canna indica (Bandera Espanola). PCR assays confirmed BBTV infection in these symptomatic test plants, as well as in Curcuma longa (turmeric) which exhibited large chlorotic blotches on the leaf. BBTV was detected from both seeds and germinated seedlings of artificially inoculated and field-collected C. indica samples. This study identified M. laterita as a new host of BBTV. The susceptibility to BBTV of M. coccinea, M. velutina, C. indica, and C. longa was also confirmed. The study also provided the first evidence of seed transmission of BBTV. C indica is an ornamental plant popularly used for landscaping in the Philippines and seeds were shown to be an efficient mode of transmission of the virus with rates up to 34%. The discovery of natural infection in ornamental plants and seeds poses a risk to the banana industry and responsible propagation and appropriate quarantine protocols must be implemented.